1997
DOI: 10.1007/bf02461482
|View full text |Cite
|
Sign up to set email alerts
|

A review of teacher development reforms in Indonesian secondary science: The effectiveness of practical work in biology

Abstract: Science teaching in Indonesia has undergone major reforms since independence. This paper examines the role of practical activities in secondary science from an international perspective and contrasts this with a developing country perspective. In examining major curriculum and teacher training reforms in Indonesia, continuing influences on science education from industrialised countries are acknowledged; however, unlike many other developing countries, Indonesia has essentially implemented curriculum and teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 14 publications
0
12
0
5
Order By: Relevance
“…Untuk yang pertama lebih dikenal sebagai kurikulum sains dimana siswa mempelajarinya dari buku teks dan pengajaran secara klasikal di kelas. Studi yang dilakukan oleh Thair dan Treagust (1997;1999) menunjukkan kecenderungan kurikulum sains negara berkembang seperti Indonesia, karena ketiadaan pakar disain dan implementasi kurikulum maka yang terjadi adalah adopsi kurikulum sains dari negara maju tanpa banyak upaya untuk adaptasi dengan kondisi lokal. Kemunculan KTSP (kurikulum tingkat satuan pendidikan) di tahun 2006 bisa dilihat sebagai dibukanya peluang kontekstualisasi terhadap isi kurikulum di tingkat sekolah.…”
Section: Pendahuluanunclassified
See 3 more Smart Citations
“…Untuk yang pertama lebih dikenal sebagai kurikulum sains dimana siswa mempelajarinya dari buku teks dan pengajaran secara klasikal di kelas. Studi yang dilakukan oleh Thair dan Treagust (1997;1999) menunjukkan kecenderungan kurikulum sains negara berkembang seperti Indonesia, karena ketiadaan pakar disain dan implementasi kurikulum maka yang terjadi adalah adopsi kurikulum sains dari negara maju tanpa banyak upaya untuk adaptasi dengan kondisi lokal. Kemunculan KTSP (kurikulum tingkat satuan pendidikan) di tahun 2006 bisa dilihat sebagai dibukanya peluang kontekstualisasi terhadap isi kurikulum di tingkat sekolah.…”
Section: Pendahuluanunclassified
“…Pada kesempatan lain ada beberapa guru yang menunjukkan kreativitasnya merancang percobaan dalam hal hukum archimides dengan menggunakan barang bekas. Suatu perkembangan positif dibanding dua dekade sebelumnya (Thair & Treagust 1997). Sedangkan sumber dari internet bisa didapat karena mayoritas sekolah yang berpartisipasi dalam riset ini mempunyai akses internet untuk digunakan oleh guru, disamping beberapa guru juga mengikuti pelatihan pengajaran internet multimedia yang menunjukkan beragamnya sumber yang bisa dimanfaatkan oleh guru dalam mencari prosedur praktikum laboratorium.…”
Section: Metodeunclassified
See 2 more Smart Citations
“…A study conducted by Abrahams and Millar (2008) suggested that laboratory activities help students to memorise practical aspects of the experiments related to natural phenomena. A review of the roles of laboratory activities for the Indonesian setting conducted three decades ago (Thair & Teagust, 1977) reported that laboratory activities promoted students' achievement in cognitive, problem solving as process skills. More recent review unfortunately are not available.…”
Section: Introductionmentioning
confidence: 99%